The influence of metal oxide powders on the physical and mechanical properties of epoxy composites for the protection of constructions made of aluminum alloys - Savchuk Petro; Matrunchyk Dmytro; Kashytskyi Vitalii; Sadova Oksana; Moroz Iryna (Lviv Politechnic Publishing House, 2019)
Protection of designs of vehicles made of aluminum alloys is an urgent application problem because these alloys are being extensively destroyed under the influence of aggressive environments, climatic factors, cyclic changes of temperature, the influence of the flow of abrasive particles. The protective coating increases significantly duration of operation of the construction and reduce the number of overhaul operations associated with restoring the surface of the product. However, there is a problem associated with the complexity of the coating technology on the constructions made of aluminum alloys, because these surfaces are inert due to the presence of oxide films. To ensure reliable protection of the surface of the construction, it is necessary to provide high adhesion strength of coating with substrate, cohesive strength and corrosion resistance of the coatings. An effective solution to this problem is the use of polymer coatings based on epoxy resins, characterized by high adaptability, specific strength, high operated properties. The use of epoxy oligomers as a polymeric matrix allows you to meet the requirements, however, it requires the development of composition of epoxy composite material and coatings technology. The purpose of the work is determination of the influence of highly dispersed powders of metal oxides on the structuring process and mechanical characteristics of epoxy omposites, and optimization of the composition for the formation of protective coatings of construction made of aluminum alloys. The classical methods of research of physical and mechanical characteristics of epoxy composites are used in the work: the gel fraction content, adhesion strength, compressive strength, impact energy. The optimum content of titanium oxide powder is found to be 8 wt % because these epoxy composites have the highest impact energy compared to composites having a different stoichiometric ratio of components. Considerable increase in impact energy of epoxy composites take place as a result of treatment of the composition at the mixing stage of the components with ultrasound, which ensures high uniformity of the composition and the lyophilicity of the powder particles. The developed coatings have increased adhesion strength, impact energy and compressive strength, which ensures their use as coatings of designs of vehicles made of aluminum alloys for protection against climatic conditions, abrasive wear and corrosion. A promising area of research is the introduction of modifying additives into the epoxy composites developed to increase their resistance to cyclic change of temperature and the application of treatment of the compositions in physical fields to ensure the high uniformity of the composition and increase the lyophilicity of the powder particles.
Keywords: adhesive strength, impact energy, dispersed filler, titanium oxide